“Estudio de un proceso de balanceado concentrado sólido a base de lactosuero.” - Arias Vilcacundo, Mayra Angélica (2021)
Whey is generated as a waste product from the cheese-making process; this by-product is dumped into rivers, sold, or given to small consumers to feed their animals. The possibility of taking full advantage of the whey in the production of a concentrated balance was studied, thus avoiding contamination since it has a rapid decomposition. The purpose of this work is to manufacture a whey-based balance to feed animals. This work has a descriptive approach since the characteristics of the whey were analyzed, described, and studied as a complement in the feeding of animals; also the causal or quasi-experimental method was used, variables were managed, through which data were obtained; the types of whey obtained in the cheese-making process were analyzed for their incorporation in the manufacture of balanced products; the whey's nutritional concentration was also determined for the formulation of the balance, which was incorporated into the diets of the animals after a physical-chemical analysis of the whey that was used managing to elaborate a formulation for their feeding. To know the results, two pigs were fed with the same portions of food, but with different formulations, Pig 1 was fed with the formulation based on whey plus cereal and Pig 2 with a standard balanced on the market; at the end of the stages, 77% weight gain was obtained in live kilograms in Pig 1 (82.60 kg) compared to the initial weight of 16.81 kg. in just 12 weeks with the whey-based formulation. The production costs are low, with the whey-based concentrated balance, the final production cost was 82.75 dollars, and with the standardized balance of the market, it is 104.16 dollars, a difference of 21.5 dollars than in a "Piara" is a significant saving..